Peranan Dinas Lingkungan Hidup Provinsi Jawa Timur dalam Pengawasan Ketaatan Lingkungan Tidak Langsung Industri Transportasi di Kota Madiun Jawa Timur - Muhammad Rizha Fahry; Mohammad Mirwan (Yayasan Literasi Sains Indonesia, 2023)
Transportation plays a role in human life. One of the transportation activities is moving goods from one place to another. Transportation can support human activities to be faster and easier. Examples of transportation activities are motor vehicles, cars, conveyors, and the like. The results of these activities produce waste, one of which is liquid waste in the form of liquid and usually this type of liquid waste is very risky to pollute the environment. For one industry, liquid waste generally consists of solid waste materials, organic waste materials and inorganic waste materials left over from production, while household/domestic waste can be in the form of dirty water from bathing, washing and toilet use. The research objective is to determine environmental compliance by conducting Indirect Supervision of the Transportation Industry in the City of Madiun, East Java, namely the Waste Quality Standards, the parameters used and the Standard Quality Standard Regulations used. This study used a quantitative-descriptive research methodology, namely research that only describes the contents of a variable in the study, not intended to test a particular hypothesis. Then from the results of the Evaluation of the East Java Province Environmental Service for the Transportation Industry it has compliance status by conducting a Wastewater Sample Test to a Laboratory that has a National Accreditation Committee (KAN) and is checked regularly once a month by fulfilling the Quality Standards in accordance with: Regulations Minister of Environment and Forestry of the Republic of Indonesia Number P.68/Menlhk/Setjen/Kum.1/8/2016 Concerning Domestic Waste Quality Standards